Permasalahan Dalam Hak Pilih Dan Memilih - Ade Zelda Savitri Siregar; Emilia Susanti; Meylani Eka Putri; Saidatul Khoiriah; Widi Anggraini (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2024)
This publication addresses topics related to electoral processes and suffrage. Its objectives include elucidating the principles of voting and suffrage, discussing challenges associated with voting rights during elections, and examining citizens' passive voting rights. The journal employs library research methodologies, involving the collection and analysis of materials from various literature sources.